2010
DOI: 10.1038/ki.2009.552
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of baseline serum vascular endothelial growth factor and neutrophil gelatinase-associated lipocalin in advanced kidney cancer patients receiving sunitinib

Abstract: To identify factors that might predict response to sunitinib in patients with renal cell carcinoma, we measured serum vascular endothelial growth factor (VEGF) and neutrophil gelatinase-associated lipocalin (NGAL) levels. A total of 85 patients were selected and, using the Motzer classification, 46 were assigned to the good- and 38 to the intermediate-risk groups. With univariate Cox analysis, both baseline serum VEGF and NGAL titers, determined by enzyme-linked immunosorbent assay, significantly predicted pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 23 publications
6
63
1
Order By: Relevance
“…Its evaluation as a urine biomarker of renal cell carcinoma has not been reported previously. Although NGAL may not be a suitable biomarker of primary kidney cancer, a recent study found it may be used as a serum biomarker to follow the efficacy of treatment in patients with metastatic kidney cancer [39]. Our study shows that uNGAL excretion, although statistically significant, is clinically insignificant as NGAL concentrations were greater than those of controls in only 8 of 67 cancer patients.…”
Section: Discussionmentioning
confidence: 38%
“…Its evaluation as a urine biomarker of renal cell carcinoma has not been reported previously. Although NGAL may not be a suitable biomarker of primary kidney cancer, a recent study found it may be used as a serum biomarker to follow the efficacy of treatment in patients with metastatic kidney cancer [39]. Our study shows that uNGAL excretion, although statistically significant, is clinically insignificant as NGAL concentrations were greater than those of controls in only 8 of 67 cancer patients.…”
Section: Discussionmentioning
confidence: 38%
“…Baseline VEGF levels have been suggested to predict anti-tumor response to high-dose IL-2 and to VEGFR-targeted therapies [34,35]. In this study, no significant association between baseline VEGF levels and clinical efficacy endpoints (ORR or PFS) was observed (Additional file 1: Table S1).…”
Section: Resultsmentioning
confidence: 62%
“…Unfortunately, the role of circulating VEGF and other clinical or molecular markers predictive of response to TKIs are still controversial [25]. The prognostic role of circulating tumour cells (CTCs) have been demonstrated in breast cancer [26] and other neoplasms, while their significance in RCC is still debated.…”
Section: Discussionmentioning
confidence: 99%